The Innovation Resistance Model of Mobile Payments for Micro and Small Enterprises - Widayani, Anna; Fiernaningsih, Nilawati (BRILIANT: Jurnal Riset dan Konseptual, 2022)
The development of digital technology currently directs people to transact using mobile payments. An efficient payment process or one of them is known as Mobile Payment has its own market compared to the three other services offered by Fintech. This strongly supports the development of the digital economy in Indonesia. This study tries to formulate a conceptual framework and research model developed with the theory of innovation resistance. Methods and models of conceptual formulation are carried out in several stages; literature study, model adoption, and instrument development. Based on theoretical and empirical studies on Innovation Resistance, this study describes the constructs and propositions used as the basis for building a conceptual model. The results of the instrument development can be used for further research.